Numerical Solutions with Linearization Techniques of the Fractional Harry Dym Equation - Yokus, Asif; Gulbahar, Sema (Walter de Gruyter Gmbh, 2019)
In this study, numerical solutions of the fractional Harry Dym equation are investigated. Linearization techniques are utilized for non-linear terms existing in the fractional Harry Dym equation. The error norms L-2 and L-infinity are computed. Stability of the finite difference method is studied with the aid of Von Neumann stabity analysis.
Keywords: Harry Dym equation; finite difference method; von Neumann stability analysis